Optimization of SMOTE Application for Classification Accuracy of Heart Disease Risk Using Artificial Neural Network - Ibnu Sarky, Fauzan; Poerwandono, Edhy (Yayasan Kawanad, 2025)
Heart disease remains a leading cause of mortality worldwide, including in Indonesia, and is often difficult to detect at an early stage. One of the main challenges in the Indonesian healthcare system is the lack of fully digitalized data management and the issue of imbalanced patient datasets, which reduce classification accuracy. This study developed a web-based information system designed to manage patient records and automatically classify heart disease risk. The system was implemented using the CodeIgniter framework with a MySQL database, and applied an Artificial Neural Network (ANN) in combination with the Synthetic Minority Over-sampling Technique (SMOTE) to address data imbalance. A total of 60 secondary patient records were processed through preprocessing, data balancing, model training, and cross-validation. Experimental results demonstrated that the application of SMOTE improved model sensitivity, with performance metrics of 87.4% accuracy, 85.2% precision, 88.6% recall, and an AUC-ROC of 0.94. These findings confirm that integrating ANN and SMOTE into a web-based system enhances classification reliability and supports faster medical decision-making. However, the study also acknowledges certain limitations, including the restricted dataset size and the absence of validation in real clinical environments. Future work should expand the dataset, test the system in healthcare facilities, and compare performance with other algorithms such as Random Forest or SVM to identify the most optimal predictive model.